RETURNS TO INVESTMENTS IN COCOA RESEARCH IN NIGERIA (1978)
The low level of agricultural productivity in many countries of the Third world constitutes a drag on economic development. In any effort to break the deadlock technological change is sine qua non. “Aid” and “technical assistance” have proved generally disappointing as means of stimulating change increasingly, developing countries have become painfully aware that development has to be internally generated In this whole process scientific and technological research is of crucial significance. The organisation of agricultural research in Nigeria is examined and its impact on agricultural productivity evaluated. It is concluded that the performance of agricultural research has been generally poor. However there seems to be some notable exception. The phenomenal increase in cocoa output over the years has often been linked, among other factors, with the introduction of improved varieties and control of pests and diseases. There is thus some indication that cocoa research may have been productive in the past. But how significant has been the contribution of research to cocoa output? Can the value of such contribution vis-a-vis its costs stand the test of social profitability? This study attempts to estimate empirically the returns to investments in cocoa research in Nigeria. For this purpose two models are developed. The first is the index-number model in which the productivity index of improved cocoa varieties is used to measure the downward shifts in the long-run cocoa supply function as a way of estimating the annual values of resource "savings” resulting from increased productivity. The annual 'values of resource savings (representing the social returns) are then weighed against the costs in terms of annual research (including extension) expenditures. The estimated internal rate of return from the resulting cash flow is found to be very high. The second model is a production function incorporating research (including extension) expenditure as an explanatory variable. The result of regression analysis on time series data indicates a high level of significance for the research variable. Converting the research coefficient into an internal rate of return the result obtained corroborated that of the index-number approach. A major implication of the findings is that there has been gross under-investments in cocoa research in the past. It thus deserves a greater share of resources on grounds of allocative efficiency. Furthermore, given the high pay-offs from investments in cocoa research, it could serve as a model in terms of organizational structure, system of financing, staff recruitment and training policy, etc., thus providing valuable insights into more effective means of mobilising scarce resources for greater productivity in the lagging sectors of agricultural research.